7 - L'Ajustement structurel dans le Tiers Monde: by Fayçal Yachir - Fayçal Yachir, (Africa Development, 1991)
For several years now, adjustment has become the key-word in economic policies in Third World countries. Development policies have been replaced by adjustment policies initiated either by governments themselves or imposed by the International Monetary Fund within the conditionality framework. After defining what adjusting an economy means , the author describes its mechanisms and objectives and then evaluates it. The evaluation is globally negative because structural adjustment policies did not succeed in correcting the internal and external financial desequilibria. There are three major reasons to the collapse of these policies : bad economic policies and options, discrepancy between the IMF doctrine and the objective conditions of operation of capitalism in the third world and faith in a number of myths (myth of national market, myth of efficiency of the private sector, myth of carelessness of the public sector and myth of comparative advantage). Therefore it is important to try alternative adjustment policies which would take into account economic rationale based on economizing the scarce resources available. The implementation of unorthodox adjustment policies in a few Latin American countries such as Mexico, Brazil, Argentina and Peru is part of this process. The prerequisites for the success of structural adjustment programs are the following : political democratization, rationalization of and opposition to neo- liberal dogmatism, opposition to market determined prices for its sake, opposition to free-exchange and to passive submission to foreign decision-making centers, opposition to reduction of standard of living of the majority and to the accumulation of revenues in the hands of a minority. It is also important to drop obsolete state capitalisms and to create new forms of articulation amongst the different sectors of economic life.